The Influence of Role Overload and Role Conflict, and Independence on the Performance of Auditors Moderated by Spiritual Intelligence of Auditors in Public Accountants - Masruroh, Aryl; Hermanto, Suwardi Bambang; Ardini, Lilis (Archives of Business Research, 2021)
Auditor performance is the result of work achieved by the auditor in carrying out his duties, in accordance with the responsibilities given and become one of the benchmarks used to determine whether a job done will be good or vice versa. Auditor performance is a major concern, both for clients and the public, in assessing the results of audits conducted. Not optimal performance of auditors in carrying out their role as auditors can cause violations committed by auditors in Indonesia. Some of the possible causes of this occurrence based on previous research are due to the existence of Role Overload, Role Conflict, and independence experienced by the auditor in carrying out his duties. The purpose of this study is to determine the factors that influence the performance of auditors working in public accounting firms in Surabaya. The analysis technique used is Moderate Regression Analysis Results. The results of this study include Role Overload and Role Conflict negatively affect Auditor Performance, Independence has a positive effect on Auditor Performance, Spiritual Intelligence weakens the influence of Role Overload and Role Conflict on Auditor Performance, and Spiritual Intelligence strengthens the influence of Independence on Auditor Performance.